Experimental demonstration of thermally tunable Fano and EIT resonances in coupled resonant system on SOI platform - Littlejohns, Callum George (2019)
Thermally tunable Fano and electromagnetically induced transparency (EIT) resonances are theoretically and experimentally demonstrated based on a Mach-Zehnder interferometer assisted Bragg grating-microring coupled resonant system on silicon-on-insulator (SOI) platform. In this paper, the destructive and constructive coupling between the two resonators, the microring resonator and the Fabry-Perot resonator formed by two Bragg gratings, give rise to the Fano and EIT resonances, respectively. The resonance lineshape can be controlled and converted by tuning the optical path length of the MZI arm. The device performance has been theoretically analyzed by using a specially developed numerical model. The coupled resonant system was designed, fabricated, and characterized on a commercial (SOI) platform. The tuning and conversion of the resonance lineshape by thermo-optical effect have been experimentally observed and verified, with good agreement between the experimental data and the simulations.